Editorial - Kallurkar, S. P. (Journal of Engineering Education Transformations, 2009)
Change is the only constant thing in our life; hence one must change with the change. Otherwise the Change will change us and then that change is very costly. This philosophy needs to be considered very seriously by the teaching community especially the engineering teachers in the light of present day scenario.